REGIONAL ANESTHESIA Ultrasound Increases the Success Rate of Spinal Needle Placement through the Epidural Needle During Combined Spinal-epidural Anesthesia. Issue 1 (March 2022) - Tao, B.; Liu, K.; Ding, M.; Xue, H.; Li, X.; Zhao, P.
Abstract : ( Eur J Anaesthesiol . 2021;38:251–258. doi: 10.1097/EJA.0000000000001380) Successful combined spinal-epidural anesthesia (CSEA) during cesarean section is important, and ultrasound-assisted placement may improve patient safety and satisfaction compared with placement using anatomic landmark palpation. This study specifically investigates whether ultrasound imaging before CSEA increases the first-pass success rate for spinal needle placement through the epidural needle.